Effect of Integration of Bio-fertilizers on the Growth and Yield of Mung Bean - Rasali, Priyanka; Bhandari, Laxmi; Ghimire, Sita Ram; Rajbanshi, Devraj; Bohara, Binod; Chaudhary, Archana; Gaha Magar, Sangita (Journal of Tikapur Multiple Campus, 2025)
Nutrient management is one of the major constraints in the production of mung bean. The experiment was conducted at the agronomy farm of Far Western University, Tikapur, Kailali from April to June 2024 to study the effect of integration of biofertilizers on the growth, yield and yield attributes of mung bean. The field was laid out in a randomized complete block design with seven treatments and three replications. The treatments were control (T1), Rhizobium (T2), Azotobacter (T3), Phosphate Solubilizing Bacteria (T4), Rhizobium + PSB (T5), Azotobacter + PSB (T6) and Rhizobium + Azotobacter + PSB (T7) along with recommended dose of chemical fertilizers and FYM. Results revealed the significant effect of biofertilizer integrations on plant height, root length, number of branches, effective and non-effective nodules, fresh shoot weight, fresh and dry root weight, root volume, pods plant-1, Seeds pod, pod length, grain yield and biological yield, however, non-significant effect was overlooked on harvest index and 1000 grain weight. The maximum significant values for growth and yield parameters were observed with the combination of Rhizobium + Azotobacter + PSB indicating increased grain yield by 23.94% compared to control. Both single inoculation and combination of biofertilizers out-performed the control. Seed treatment either with Rhizobium or Azotobacter remained economically feasible compared to other treatments and hence is recommended to extrapolate the finding.